RIGS16-150-0314/ A pilot study on cyclic process approach for disposing Islamic literature material - Zainan Nazri, Nurul Jannah; Gasmelsid, Saadeldin Mansour; Samsudin, Sofiah; Azman, Amelia Wong; Mohammed Yaqub, Mohammed Abullais Shamsuddin (RMC, 2018)
The advancement of the technology in printing media has led to the increasing number of paper-based published Islamic literature materials. Eventually, the demand to provide a means of disposing unused published materials has also increased. In Malaysia alone, according to the latest statement of JAKIM, JAIS and JAWI, they are not able to accept any unused published Islamic literature materials for disposal for the time being due to the large volume at the collection center. Based on our early research, we perceive that the present fatwa and guidelines in Malaysia which restrict the disposal method to only burning and disseminating the ashes into the sea as the main reason behind the bottleneck problem at the collection center. On top of that, given the large amount of material to be disposed, we believe that this method is not environmentally friendly. Statistics have shown that burning of any material which occurs around the globe has worsened the air quality index. It is an Islamic teaching to preserve the environment, hence, a more sustainable disposal method for the Islamic literature material must be identified and explored. This study is timely as it aims to review the present fatwa and guidelines throughout Malaysia related to disposing Islamic literature materials. This work also aims to propose a new comprehensive guidelines and to identify other sustainable means for disposing Islamic literature materials besides burning and disseminating the ashes into the sea. The study will begin with analytical method to explore the existing fatwa and guidelines available throughout Malaysia in order to rectify their loopholes especially with regards to inculcating sustainable and efficient method of disposing Islamic literature material. Then by embracing inductive method the researchers will sort out all related Qur’anic verses, Prophetic hadith and athar of the Companions and Successors related to this issue. This will be followed by understanding and comprehending the selected interpretations of Quranic verses from classical and modern Muslims exegetes as well as the most authoritative commentaries on the hadith and athar. Deductive method is used in proposing a new comprehensive guidelines and identifying other sustainable means for disposing Islamic literature materials. It is cognizant to mention here that the present fatwa and guidelines in Malaysia related to this issue is based on ijtihad and Masalih Mursalah (unrestricted public interest) principles. It is not fix tawqifi (unchanged) matter but it opens to any amendment, supplement and enhancement based on the Masalih Mursalah principle.